In Vitro and In Situ Evaluation of Fermented High Moisture Corn and Ear Corn as Alternative Feedstuffs for Feedlot Calves - Rajaei-Sharifabadi, H.; Villalba, D.; Mora, J.; de la Fuente, G.; Balcells, J.; Seradj, A. R. (Tropical Animal Science Journal, 2025)
High-moisture corn products offer potential advantages in intensive cattle feeding systems by providing high-energy feedstuffs while allowing earlier harvest. This study evaluated the nutritional value and fermentation characteristics of fermented high-moisture grain corn (HMG) and high-moisture ear corn (HME) compared to conventional corn grain (CG) and corn silage (CS) through in vitro and in situ techniques. Six samples from each corn product were collected from commercial farms, pooled, and analyzed in five replicates. Chemical analysis revealed that HME contained higher neutral detergent fiber (19.0% vs. 4.25%) but lower starch (60.95% vs. 66.75%) and crude protein (7.27% vs. 8.32%) compared to HMG (p